2022
DOI: 10.48295/et.2022.87.2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact assessment of passenger ferries and cruise vessels: the case study of Crete

Abstract: Year 2020 was a milestone year for shipping both positively and negatively: the insecurity of people to move freely due to the Covid-19 pandemic imposed travel restrictions, while on the other hand the enforced Directives and Regulations (i.e. fuel sulfur standards) contribute to the reduction of harmful air emissions from shipping. The scope of the paper is to present some important findings regarding induced air emissions in ports due to shipping activities. Two Greek major ports have been used as a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…When compared to diesel and biogas powered buses, electric buses offer significant savings in societal cost and total cost of ownership, mainly due to decreased noise, no emissions while in use, and decreased energy costs (Borén, 2020). The shift towards electrification for passage and freight transportation has been emphasized by various researchers around the world (Dhonde & Patel, 2020;Doundoulakis et al, 2022;Fistola et al, 2021;Borghetti et al, 2022). In the study by Sharma and Chandel (2020), they concluded that EVs may reduce air pollution most when they operate on more efficient batteries charged from renewable energy sources, as CO2 emissions will drop by at least 29% across all vehicle classes additionally, and by 2050, EVs could achieve CO2 emission reductions of 14-100% if the electricity is generated from renewable resources significantly.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to diesel and biogas powered buses, electric buses offer significant savings in societal cost and total cost of ownership, mainly due to decreased noise, no emissions while in use, and decreased energy costs (Borén, 2020). The shift towards electrification for passage and freight transportation has been emphasized by various researchers around the world (Dhonde & Patel, 2020;Doundoulakis et al, 2022;Fistola et al, 2021;Borghetti et al, 2022). In the study by Sharma and Chandel (2020), they concluded that EVs may reduce air pollution most when they operate on more efficient batteries charged from renewable energy sources, as CO2 emissions will drop by at least 29% across all vehicle classes additionally, and by 2050, EVs could achieve CO2 emission reductions of 14-100% if the electricity is generated from renewable resources significantly.…”
Section: Discussionmentioning
confidence: 99%